The silicon tutor: is AI enhancing education or outsourcing the mind? - Zavadskykh, Denys; Завадських, Денис (Запоріжжя: ТДАТУ, 2026)
By 2026, the integration of Artificial Intelligence (AI) into higher education has transitioned from an experimental novelty to a structural necessity. Large Language Models (LLMs) are now heavily utilized by university students to navigate complex research, structure analytical writing, and generate code. This ubiquitous adoption fundamentally alters the academic paradigm, institutions to determine where cognitive development ends and algorithmic automation begins. The immediate appeal of LLMs lies in their measurable impact on academic productivity; empirical investigations indicate that access to generative algorithms can compress the time required for analytical writing tasks by up to 40% while simultaneously elevating the structural coherence of the output [1].
Keywords: silicon tutor; AI; Artificial Intelligence